Adaptation of Religion and Local Wisdom in Global Environmental Issues in Indonesia - Syafwan Rozi; Zulfan Taufik (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2020)
This study focuses on how the adaptation efforts and survival strategies of local communities in Indonesia to the non-natural pressure on nature and the value of their local wisdom in protecting and preserving the environment. Anthropological, ecological, and related literature on local communities are used as a review and analytical framework. The selected local communities are the Mentawai tribe, the slopes of Mount Merapi, and the Balinese in Indonesia. These three case studies show that the adaptations and strategies carried out by local communities are diverse and have different knowledge implications. The Mentawai tribe in maintaining the tradition of arat sabulungan and Balinese in revitalizing Wariga can adjust and adapt well when faced with natural ecological cycles and non-natural penetration. That is because its application is more flexible, practical, and intellectual than putting forward the device of beliefs and myths. While the case of the local community on the slopes of Merapi, which has local significance in the form of cosmological teachings in disaster management, tends to prioritize faith that is rooted more in myth than knowledge related to the objective world. Therefore, when this set of knowledge in local wisdom struggles to surpass marginalized status, the two cases of the Mentawai and Balinese communities can become persuasive and adaptive. In contrast, the local community on the slopes of Merapi is more challenging to adapt. The study also recommends that it is time for traditional knowledge originating from local wisdom in Indonesia to be adapted, modified and used as an essential resource in managing contemporary environmental issues effectively and collaboratively.